The perceived value of athlete monitoring to elite sport practitioners - Neupert, E. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Athlete monitoring systems (AMS) can aid performance optimisation and injury prevention, but recently their efficacy has been questioned. The perceived value of monitoring matters, because if practitioners lack confidence in their monitoring systems, their ability to positively influence training programming is diminished. To address this, researchers have primarily sought to improve AMS metric-related factors e.g. measure reliability. In comparison however, the impact of socio-environment factors e.g. stakeholder buy-in on AMS, has received less attention. This study explored the perceived value of athlete monitoring by elite sport practitioners focussing on socio-environment factors. METHODS: Seventy-five elite sport practitioners (response rate: n= 30) who worked with tier 3-5 athletes (1) were invited to take part in an online survey about their athlete monitoring practices. The practitioners represented 14 different sports and 599 athletes. The survey took approximately 20 minutes to complete, with questions primarily answered by checkboxes, Likert scale responses or short answers. Spearman`s correlation coefficient was used to test the strength of Likert relations and Bonferroni corrected to p <0.017. RESULTS: Fifty-two percent (n=13) respondents were confident in the sensitivity of their athlete self-report measures (ASRM) to detect meaningful change, with 64% (n=16) indicating their ASRM was underpinned by scientific studies. Such scientific evidence was linked with improved feedback to athletes (r (23) = 0.487, p =0.014); and improved feedback correlated with better athlete monitoring adherence (r (22) = 0.675, p <0.001). If athletes did not complete their monitoring, 52% (n= 13) respondents felt the athletes` performance might be compromised. However, most respondents 56%, (n= 14) had worked with internationally successful athlete(s) who had reached the podium at major international events and did not complete their monitoring. CONCLUSION: While AMS can be a useful tool for performance optimisation, its potential value isn`t always realised. The difference between some practitioner`s beliefs; (a lack of monitoring compromises performance) versus reality; (some internationally successful athletes do not complete monitoring) indicates that the efficacy of monitoring should be regularly reviewed to ensure it is providing value. Practitioners should also consider simultaneously addressing socio-environment and metric-related factors in order to improve AMS efficacy.